Research of conditions of removal of fire protection from building construction - Tsapko, Yu.; Tsapko, A.; Bondarenkо, O. (My University, 2020)
Fireproof coatings at the time of operation of the building structure is a separate and complex task, covering both the stages of the process protection from moisture, and subsequent fire protection formed during the swelling of the coating. They have been proven to create a layer of material on the surface that prevents moisture from penetrating the wood when the destruction of the coating begins. This makes it possible to determine the effect of flame retardants and the properties of the protective compositions on the process of slowing down the rate of water absorption. The process of moisture transfer by flame retardant coating in the presence of a polymeric shell is simulated, the diffusion and mass transfer dependences are obtained, and the diffusion coefficient is determined, which is 7.08·10-12 m2/s, which allow to obtain a change in the dynamics of moisture upon washing out of the flame retardant. The results of determining the weight loss of the coating sample during exposure to water indicate the ambiguous effect of the nature of the leaching agent. In particular, this implies the availability of data sufficient for qualitatively conducting the process of inhibition of moisture diffusion and detection on its basis of the moment from which the fall of the coating efficiency begins. Features of slowing down the process of moving the moisture to the material that is treated with flame retardant, are in several aspects. Namely, the use of water-insoluble flame retardants and other components, as well as polymer binder, which are characterized by the formation of polymer shell on the surface of the wood.
Стаття
Keywords: protective agents; mass transfer; weight loss; moisture diffusion; surface treatment; protection efficiency